Effect of Treatment and Repair Engine Performance and Achievements of the Industrial Employment Practices Class XI Student Work Readiness Skills Program Engineering Machinery SMK Pancasila Kutoarjo Academic of 2012/2013 - Dwi Setiawan Nugroho; Subagyo Subagyo (Jurnal Taman Vokasi, 2013)
This study aims to determine the effect of Achievement Machinery Related to Job Readiness, to determine the effect of the Industrial Performance Work Practices and Work Readiness to determine the effect of Achievement Care and Repair Engine and Performance Practice Industrial Work together to Class XI Student Work Readiness Program Machinery Engineering expertise SMK Pancasila Kutoarjo Academic of 2012/2013.The population in this study were all students of Grade XI Skills Program Smk Pancasila Kutoarjo Machinery Engineering Academic of 2012/2013 a number of 351 students, 40% of samples taken as many as 140 students, while 30 students for the test instrument. This research study including the ex post facto, while sampling technique using a random system (random sampling). Data collection technique used to obtain the data documentation Achievement Care and Repair Engine Performance Work Practices and Industry, While the techniques used to obtain data questionnaire Job Readiness. To determine the validity and reliability of the instrument, the instrument tested first. In analyzing the data the study used the technique of partial correlation and multiple regression two predictors.            Results were obtained (1) partially positive and significant effect Achievement Machinery Related to Job Readiness and (2) partially positive and significant impact on the Industrial Performance Work Practices Work Readiness (3) is positive and significant effect regression Achievement Maintenance and Repair machinery and Industrial Performance Work Practices together to Class XI Student Work Readiness Skills Program SMK Pancasila Kutoarjo machinery Engineering Academic of  2012/2013.